2015
DOI: 10.1007/s11356-015-5507-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interpolation methods for the estimation of groundwater contamination in Andimeshk-Shush Plain, Southwest of Iran

Abstract: Selection of appropriate interpolation methods for the conversion of discrete samples into continuous maps is a controversial issue in the environmental researches. The main objective of this study was to analyze the suitability of three interpolation methods for the discrimination of groundwater with respect to the water quality index (WQI). The groundwater quality data consisted of 17 variables associated with 65 wells located in Andimeshk-Shush Plain. Three spatial interpolation methods including ordinary k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 34 publications
2
32
0
2
Order By: Relevance
“…On the contrary, EBK uses an intrinsic random function as the kriging model despite the other kriging methods. The other main difference of EBK with that of the other kriging model is that EBK does not assume a tendency toward an overall mean; thus, there is the same chance for large deviations to get larger or smaller [17].…”
Section: Empirical Bayesian Kriging (Ebk)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, EBK uses an intrinsic random function as the kriging model despite the other kriging methods. The other main difference of EBK with that of the other kriging model is that EBK does not assume a tendency toward an overall mean; thus, there is the same chance for large deviations to get larger or smaller [17].…”
Section: Empirical Bayesian Kriging (Ebk)mentioning
confidence: 99%
“…Higher weighting values are assigned to those points, which are closer to the interpolated points. As the distance increases, the weight decreases, and u is the weighting power that imposes the amount of weight decreases with respect to the increase in distance [17,18].…”
Section: Inverse Distance Weighting (Idw)mentioning
confidence: 99%
See 1 more Smart Citation
“…Directly, during sampling, the groundwater level was measured. Statistically analysed were conducted with software package Statistica version 13.0 (Statsoft 2015) as well as deterministic spatial interpolation method (IDW -Inverse Distance Weighting) was applied [24,25]. Spatial interpolation was performed using the ArcGIS Spatial Analyst.…”
Section: The Research Object Characteristicmentioning
confidence: 99%
“…These methods include, among others, the use of some auxiliary variables, such as elevation and distance to coastline, to integrate in the multivariate geostatistics and the application of empirical Bayesian kriging (EBK) for spatial interpolation of monthly rainfall. Currently, the analysis of scientific literature shows that the use of EBK in studies dealing with the interpolation of hydrological variables can be found only in Mirzaei and Sakizadeh (2016) and Gupta et al (2017). In the latter case, EBK was compared to OK methods in the interpolation of rainfall data.…”
Section: Introductionmentioning
confidence: 99%